Rational Design and Synthesis of Modified Teixobactin Analogues: In Vitro Antibacterial Activity against Staphylococcus aureus, Propionibacterium acnes and Pseudomonas aeruginosa. Issue 36 (6th June 2018) - Ng, Vivian; Kuehne, Sarah A.; Chan, Weng C.
Abstract: Teixobactin, a recently discovered depsipeptide that binds to bacterial lipid II and lipid III, provides a promising molecular scaffold for the design of new antimicrobials. Herein, we describe the synthesis and antimicrobial evaluation of systematically modified teixobactin analogues. The replacement of the Ile 11 residue with aliphatic isosteres, the modification of the guanidino group at residue 10 and the introduction of a rigidifying residue, that is, dehydroamino acid, into the macrocyclic ring generated useful structure–activity information. Extensive antimicrobial susceptibility assessment against a panel of clinically relevant Staphylococcus aureus and Propionibacterium acnes strains led to the identification of the new lead compound, [Arg(Me) 10, Nle 11 ]teixobactin, with an excellent bactericidal activity (minimum inhibitory concentration (MIC)=2–4 μg mL −1 ). Significantly, the antimicrobial activity of several of the teixobactin analogues against the pathogenic Gram‐negative Pseudomonas aeruginosa was "restored" when combined with the sub‐MIC concentration of the outer membrane‐disruptive antibiotic colistin. The antimicrobial effectiveness of a [Tfn 10, Nle 11 ]teixobactin (32 μg mL −1 )–colistin (2 μg mL −1 ; 0.5×MIC) combination against P. aeruginosa PAO1 reveals, for the first time, an alternative therapeutic option in the treatment of Gram‐negative infections. Abstract : Breaking through the superbugs ! Teixobactin analogues utilised in two different approaches were found to be potential solutions to both Gram‐positive and Gram‐negative infections.